2009
DOI: 10.1002/uog.7342
|View full text |Cite
|
Sign up to set email alerts
|

Gestational sac volume: comparison between SonoAVC and VOCAL measurements at 11 + 0 to 13 + 6 weeks of gestation

Abstract: Objectives To assess the novel three-dimensional (3D) tool, Sonography-based Automated Volume Count TM (SonoAVC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Their results suggest that SonoAVC significantly underestimates fluid volume. By contrast, Borenstein et al showed that the GS FV was comparable in measurements derived with SonoAVC and VOCAL, using 15° rotation steps, in pregnancies between 11 and 14 weeks11. Closer inspection of these data, however, reveals that the mean differences in GS FVs obtained by the two techniques varied by 1–5 cm 3, 24.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Their results suggest that SonoAVC significantly underestimates fluid volume. By contrast, Borenstein et al showed that the GS FV was comparable in measurements derived with SonoAVC and VOCAL, using 15° rotation steps, in pregnancies between 11 and 14 weeks11. Closer inspection of these data, however, reveals that the mean differences in GS FVs obtained by the two techniques varied by 1–5 cm 3, 24.…”
Section: Discussionmentioning
confidence: 90%
“…In this technique, the relatively regular structures of the gestational sac (GS) and yolk sac (YS) are measured using VOCAL, and the GS fluid volume (FV) is then measured using sonography‐based Automated Volume Count (SonoAVC (GE Medical Systems)). This technique, which identifies and quantifies hypoechoic regions within a 3D dataset, and provides an automated calculation of fluid volume, has been shown to be both valid and reliable9–11. The advantage of our semiautomated technique is that it facilitates the measurement of the embryo without the need to physically define its contour, which is the prime limiting factor in the techniques described above.…”
Section: Introductionmentioning
confidence: 99%
“…Borenstein et al (21) studied 65 women undergoing routine first trimester screening between 11 þ 0 and 13 þ 6 weeks of gestation with uncomplicated singleton pregnancies. The volume of the gestational sac (GS) was measured twice with SonoAVC and VOCAL by a single investigator.…”
Section: Sonoavc In Pregnancymentioning
confidence: 99%
“…The gestational sac fluid volume (GSFV) represents the gestational sac volume (GSV) minus the volume of the embryonic parts. Until now, the GSV and the GSFV were measured in 3D by using three different volume‐measuring methods5, 13–17.…”
Section: Introductionmentioning
confidence: 99%